Effects of sex and season (breeding and non-breeding) on microhabitat selection in Stejneger’s bamboo pitviper (Viridovipera stejnegeri) - Tan,Songwen; Wu,Yayong; Wang,Jiajun; Lyu,Bing; Yu,Min; Zhang,He; Guo,Peng; Shi,Lei (PeerJ, 2025)
Habitat quality and availability are crucial for the survival and reproduction of animal species. Intraspecific and seasonal differences in habitat selection reflect adaptations to changing biological requirements and environmental factors. To investigate the effects of season (breeding and non-breeding) and sex on microhabitat selection in snakes, here we employed field surveys to analyze microhabitat selection data for Stejneger’s bamboo pitviper (Viridovipera stejnegeri) across different sexes and seasons. Results indicated that although no significant difference was observed between groups, marked differences in certain microhabitat factors were noted. Specifically: (1) Non-breeding season females (NBF) displayed distinct differences in altitude, slope position, distance from roads compared to other groups. (2) Temperature exerted a lesser effect on non-breeding season individuals compared to breeding season individuals. Additionally, distance from roads only significantly impacted breeding season males, not females. (3) Regarding sexual differences, males and females differed in slope position and distance from residential sites, reflecting their distinct ecological requirements. Regarding seasons, differences in habitat selection between breeding and non-breeding seasons were primarily related to temperature, indicating behavioral changes linked to seasons. (4) Non-breeding season females exhibited the narrowest microhabitat niche width and the least microhabitat niche overlap with other groups, potentially due to their pronounced foraging requirements, which compel them to explore limited habitats with higher human disturbance but richer food sources. This study contributes novel insights into the habitat selection behaviors of snakes.
Keywords: Microhabitat selection; Ecology; Snakes; Pitviper